A distinct plasma lipid signature associated with poor prognosis in castration‐resistant prostate cancer. Issue 10 (8th August 2017) - Lin, Hui‐Ming; Mahon, Kate L.; Weir, Jacquelyn M.; Mundra, Piyushkumar A.; Spielman, Calan; Briscoe, Karen; Gurney, Howard; Mallesara, Girish; Marx, Gavin; Stockler, Martin R.; PRIMe Consortium,; Parton, Robert G.; et al.
Abstract : Lipids are known to influence tumour growth, inflammation and chemoresistance. However, the association of circulating lipids with the clinical outcome of metastatic castration‐resistant prostate cancer (CRPC) is unknown. We investigated associations between the plasma lipidome and clinical outcome in CRPC. Lipidomic profiling by liquid chromatography‐tandem mass spectrometry was performed on plasma samples from a Phase 1 discovery cohort of 96 CRPC patients. Results were validated in an independent Phase 2 cohort of 63 CRPC patients. Unsupervised analysis of lipidomic profiles (323 lipid species) classified the Phase 1 cohort into two patient subgroups with significant survival differences (HR 2.31, 95% CI 1.44–3.68, p = 0.0005). The levels of 46 lipids were individually prognostic and were predominantly sphingolipids with higher levels associated with poor prognosis. A prognostic three‐lipid signature was derived (ceramide d18:1/24:1, sphingomyelin d18:2/16:0, phosphatidylcholine 16:0/16:0) and was also associated with shorter survival in the Phase 2 cohort (HR 4.8, 95% CI 2.06–11.1, p = 0.0003). The signature was an independent prognostic factor when modelled with clinicopathological factors or metabolic characteristics. The association of plasma lipids with CRPC prognosis suggests a possible role of these lipids in disease progression. Further research is required to determine if therapeutic modulation of the levels of these lipids by targeting their metabolic pathways may improve patient outcome. Abstract : What's new? Lipids are known to influence tumour growth, inflammation and chemoresistance. However, the association of circulating lipids with the clinical outcome of metastatic castration‐resistant prostate cancer (CRPC) is unknown. Here, the authors performed lipidomic analysis on plasma from CRPC patients and identified a three‐lipid signature associated with overall survival – elevated levels of ceramide d18:1/24:1, sphingomyelin d18:2/16:0 and phosphatidylcholine 16:0/16:0 were associated with worse outcome. The signature was independent of clinicopathological factors and metabolic characteristics, and was validated in an independent cohort. Further research is required to determine if therapeutic modulation of lipid levels associated with poor prognosis can improve patient outcome.